Technology for Deep Purification of Cesium iodide single Crystal Production Wastes from heavy metals - Grinyov, B.V.; Cherginets, V.L.; Rebrova, T.P.; Ponomarenko, N.V.; Varich, A.G.; Rebrov, A.L. (Наука та інновації, 2020)
Introduction. The production of CsI-based scintillation crystals results in accumulation of wastes formed during the crystal growth and as a result of the mechanical treatment. Therefore, thorough purification from heavy metals is the main condition of CsI recycling for the further application in obtaining the different activated single crystals.
Problem Statement. Thallium is one of the main admixtures in the wastes of CsI-based crystal production because it is used as an activating admixture for the of CsI:Tl crystals. Since Tl is referred to heavy metals which are hardly removable from the wastes of CsI crystal production the development of the purification technology of technogenic CsI solution from admixtures of heavy metals is necessary. Purpose. The development of technology providing purification of the wastes of CsI-based crystal production to the level required by national normative documentation for extra pure CsI.
Materials and Methods. Materials: the liquid wastes of CsI-based crystal production (the CsI solution), activated carbon, metallic magnesium, barium hydroxide, cesium carbonate. Methods: the treatment of mixture of the heated CsI solution with the purifier by stirring, the multiple filtering of the heated CsI through the cartridge filters filled with purifying reagents.
Results. The method for treatment of technogenic CsI solution with magnesium at heating and stirring proved to be successful under laboratory conditions, however, attempts to level it up for the industrial scale failed. Multiple filtering of the heated reagent mixture through the cartridge filters filled with purifying reagents proved to be better and led to successful industrial examinations. It gives the possibility to obtain the extra pure product, CsI, meeting requirements of TU U 24.13.31331736-002-2004 for cesium iodide.
Conclusions. A new technology for deep purifying the wastes of CsI-based crystal production from heavy metals including thallium has been developed. Вступ. Виробництво активованих сцинтиляційних монокристалів на основі йодиду цезію супроводжується накопиченням залишків вирощування і обробки кристалів. Їх ретельне очищення від домішок важких металів є головною умовою подальшого використання йодиду цезію при одержанні різних типів монокристалів активованого CsI.
Проблематика. Основною домішкою у залишках виробництва монокристалів на основі йодиду цезію є талій, оскільки TlI використовується як активатор при вирощуванні монокристалів CsI:Tl. Талій — важкий метал, домішку якого найбільш складно видалити із зазначених залишків, тому розробка ефективної технології очищення техногенних розчинів CsI від домішок важких металів є актуальною.
Мета. Розробка технології очищення залишків виробництва монокристалів на основі CsI від домішок важких металів до рівня чистоти, зазначеної у вимогах національних нормативних документів для йодиду цезію особливої чистоти.
Матеріали й методи. Як матеріал було використано розчини залишків виробництва монокристалів на основі CsI, активне вугілля, магній, гідроксид барію, карбонат цезію. Методи: обробка суміші нагрітого розчину залишків і очищувача при перемішуванні; багаторазове фільтрування нагрітого розчину залишків через патронні фільтри, заповнені очищувачами.
Результати. Метод обробки техногенного розчину йодиду цезію магнієм при нагріванні та перемішуванні є ефективним в лабораторних випробуваннях, але його застосування у виробничих умовах не дало позитивного результату. У промислових умовах ефективним виявився метод багаторазового пропускання нагрітого розчину CsI через патронні фільтри, заповнені очищувачами. Використання зазначеного методу дозволило одержати особливо чистий продукт — CsI, який за якістю відповідає вимогам ТУ У 24.13.31331736-002-2004.
Висновки. Розроблено нову технологію очищення залишків виробництва монокристалів на основі йодиду цезію від домішок важких металів, зокрема й талію.